Growth Performance and Histopathology of Clarias Gariepinus Fed Toasted Canavalia Ensiformis Diet (British Journal of Multidisciplinary and Advanced Studies, 2023)
Fish farms output and profits have been facing a greater challenge with a hike in the price of feed ingredients. This study was designed to evaluate the growth performance and histopathology of clarias gariepinus fingerlings fed Toasted Canavalia ensiformis seed meal diets.Toasted Canavalia ensiformis meals were used to formulate five different 40.0% isoproteic diets each at 0%, 25%, 50%, 75% and 100% and coded TCe, which were fed at 5% body weight to fingerlings of Clarias gariepinus fingerlings. One hundred and fifty Clarias gariepinus (0.96g±0.03 and 3.93cm±0.28) were randomly assigned to five treatments of 10 fingerlings, replicated three times in a completely randomised design (CRD) in 35L plastic circular bowls through a semi-flow-through system for 84days. Weights and lengths were measured biweekly and used to calculate the growth and nutrient utilization parameters. Histopathology of the fish organs were evaluated. Data collected were analysed using a one-way analysis of variance. Results from the statistical analysis revealed significant differences (p